Probing the electrical double layer by operando X‐ray photoelectron spectroscopy through a graphene‐carbon nanotube composite window. Issue 2 (12th May 2020) - Wang, Peng; Li, Yunfeng; Wang, Luning; Kłos, Jacek; Peng, Zhiwei; Kim, Nam; Bluhm, Hendrik; Gaskell, Karen; Liu, Ping; Lee, Sang Bok; Eichhorn, Bryan W.; Wang, YuHuang
Abstract: The electrical double layer is known to spontaneously form at the electrode‐electrolyte interface, impacting many important chemical and physical processes as well as applications including electrocatalysis, electroorganic synthesis, nanomaterial preparation, energy storage, and even emulsion stabilization. However, it has been challenging to study this fundamental phenomenon at the molecular level because the electrical double layer is deeply "buried" by the bulk electrolyte solution. Here, we report a quantitative probing of the electrical double layer of ionic liquids from the solid side of a photoelectron‐transparent graphene‐carbon nanotube hybrid membrane electrode using X‐ray photoelectron spectroscopy. The membrane window is ultrathin (1‐1.5 nm), large (~1 cm 2 ), and robust, enabling a tight seal of the electrolyte and quantitative measurement with excellent photoelectron signals. By operando monitoring the population changes of cations and anions in response to the applied electrical potentials, we experimentally resolve the chemical structure and dynamics of the electrical double layer, which corroborate results from molecular dynamics simulations. Abstract : A graphene‐carbon nanotube hybrid membrane enables an ultrathin (1‐1.5 nm), large‐area (~1 cm 2 ) and photoelectron‐transparent window for operando probing of the electrical double layer by X‐ray photoelectron spectroscopy. The results corroborate molecular dynamics simulations, clearly resolving the formation and dynamics of an electrical double layer in response to the applied electrical potentials.